(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The sunlight exposure represents one of key parameters of indoor climate comfort. The evaluation of sunlight access into buildings is based on a methodology of European standard EN 17037. The methodology is focused on specification of an insolation time which would comply with requirements for the sunlight expo sure of permanently occupied spaces like houses and residential buildings as well as schools or hospitals. The sunlight exposure evaluation is recommended to be between 1st February and 21st March. The specific date from the interval can be selected for individual evaluations. This is a relatively long period of days in which the insolation could vary meaningfully. The aim of this study is to evaluate how the sunlight exposure might be changed in the recommended standard period in dependence on the geographic locality and climatic conditions in the Central Europe region. It depends on the sunlight time and specific design situations as well as shading obstructions. The review of the sunlight exposure is determined. The review results can perform information about design possibilities for the sunlight exposure in real buildings in the given climatic locality.